Augmented reality exploration of human femur: Unveiling fractures and anatomy for enhanced understanding - Phong, Calvin Dao Jie (2025)
This proposal introduces an innovative Augmented Reality (AR) application, "Augmented Reality Exploration of Human Femur," aimed at revolutionizing the understanding and analysis of femur fractures. Traditional methods of studying femur anatomy often lack the interactivity and precision needed for detailed exploration, which this AR application seeks to address. By integrating advanced AR technology with meticulously crafted 3D models, the application will allow medical professionals, educators, and students to virtually dissect and examine the femur in real-time, enhancing the comprehension of its complex structures and fractures. The development will be conducted using Unity, with Blender refining the 3D models for anatomical accuracy, and C# programming executed in Microsoft Visual Studio. Firebase will support data storage and management, facilitating user interactions and educational modules. The expected outcome is a user-friendly, immersive tool that sets new standards in medical education and clinical practice, improving diagnostic accuracy and treatment planning.